Consent for clinical research in the neonatal intensive care unit: a retrospective survey and a prospective study. Issue 4 (1st July 2003) - Burgess, E; Singhal, N; Amin, H; McMillan, D D; Devrome, H
Abstract : Background: Recruitment into research studies in the neonatal intensive care unit has been problematic. Therefore suggestions have been made to take decision making about enrolment out of the hands of the parents. Objective: To understand parental perceptions of the process of recruitment and enrolment for research in the neonatal intensive care unit. Method: A questionnaire was developed and used in both a retrospective survey and a prospective study of parents whose newborns were enrolled in trials in a neonatal intensive care unit. Closed ended and open ended questions were included, as well as demographic questions. Results: The retrospective survey had a 79% response rate (29 of 38). Overall, 90% of parents felt that they had made informed decisions, and 93% were against the option that a doctor decide if the newborn should be enrolled into a study, rather than the parent. Although some parents (38%) found that recruitment did add "stress to an already stressful situation", 90% felt that they had made informed decisions and understood the elements of the study. Most parents had been requested to enrol their newborn into more than one trial, and, on average, they thought that they would be comfortable with enrolment into two studies (range 0–6). When asked how the process could be improved, parents suggested that information be made available before delivery. The responses of parents in the prospective study were mostly consistent with those from the retrospective survey. Conclusions: Overall the parents did not support the suggestion that decision making about enrolment be taken away from parents and put into the hands of doctors. The healthcare team should support parents in their role of decision maker, enhance availability of the research staff, and provide more information about the research.